WeChat-based mHealth intention and preferences among people living with schizophrenia - Xiao,Shuiyuan; Li,Tongxin; Zhou,Wei; Shen,Minxue; Yu,Yu (PeerJ, 2020)
Background The past few decades have seen a rapid expansion of mHealth programs among people with serious mental illness, yet mHealth for schizophrenia is in a much earlier stage of development. This study examined the intention of WeChat-based mHealth programs among people living with schizophrenia (PLS) and evaluated correlates of the intention. Methods A total of 400 PLS aged 18–77 completed a cross-sectional survey by face-to-face interviews. The survey included a general question asking about participants’ willingness to attend WeChat-based mHealth programs, followed by preferences of three specific WeChat-based programs: psychoeducation, peer support, and professional support. PLS symptoms, functioning and disability were measured using the 18-item Brief Psychiatric Rating Scale (BPRS-18), the Global Assessment of Functioning (GAF), and the 12-item World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0), respectively. A multivariate logistic regression was used to determine correlates of program participation intention. Results Over forty percent (43%, n = 172) of participants were willing to participate in WeChat-based mHealth programs, among whom preferences for each specific program were shown in descending order: psychoeducation (68.60%), professional support (60.47%), and peer support (52.33%). A multivariate analysis revealed that younger age (OR: 0.13–0.20, 95% CI [0.05–0.43]), higher education (OR: 3.48–6.84, 95% CI [1.69–18.21]), and lower disability (OR: 0.97, 95% CI [0.94–0.99]) were all independently associated with WeChat-based mHealth program participation intention. Conclusion The findings provide guidance for further development of WeChat-based mHealth programs among PLS in China, and targeted at those who are younger, well-educated and with lower disability.
Keywords: Schizophrenia; WeChat; mHealth; Intention; Preferences; Chinese